Primary care micro-teams: a protocol for an international systematic review to describe and examine the opportunities and challenges of implementation for patients and healthcare professionals - Coombs, CRH; Cohen, T; Duddy, C; Mahtani, KR; Roberts, N; Saini, A; Foster, AS; Park, S (BMJ Publishing Group, 2022)
Introduction: There has been a recent trend towards creating larger primary care practices with the assumption that interdisciplinary teams can deliver improved and more cost-effective services to patients with better accessibility. Micro-teams have been proposed to mitigate some of the potential challenges with practice expansion, including continuity of care. We aim to review the available literature to improve understanding of how micro-teams are described and the opportunities which primary care micro-teams can provide for practice staff and patients and limitations to their introduction and implementation. Our review asks: how is micro-team implementation described? What are the experiences of healthcare professionals and patients concerning micro-teams in primary care? What are the reported implications of micro-teams for patient care? Methods and analysis: CINAHL, Cochrane Library, Embase, MEDLINE and Scopus will be searched for studies in English. Grey literature will be sourced from Google Scholar, government websites, CCG websites, general practice directives and strategies with advice from stakeholders. Included studies will give evidence regarding the implementation of micro-teams. Data will be synthesised using framework analysis. We will use iterative stakeholder and public and patient participation to embed the perspectives of those whom micro-teams could impact. Included studies will be quality assessed using the Mixed Methods Appraisal Tool. The quality assessment will not be used to exclude any evidence but rather to develop a narrative discussion evaluating included literature. Ethics and dissemination: Ethical approval will not be necessary for this systematic review as there will only be a secondary analysis of data already available in scientific databases and the grey literature. This protocol has been submitted for registration to be made available on a review database (PROSPERO). Findings will be disseminated widely through peer-reviewed publication and in various media, for example, conferences, congresses or symposia. PROSPERO registration number: CRD42021225367.